The Effect of Using Powtoon Animation Learning Media on Solar System Material on the Learning Outcomes of Class VI Elementary School Students - Istiqomah Istiqomah; Banu Setyo Adi (Jurnal Penelitian Pendidikan IPA, 2024)
The research aims to examine the significant influence of using Powtoon learning media on the learning outcomes of class VI students at SDN 21 Muntok. Sampling used the purposive area sampling method and obtained two classes, namely VI A experimental  class and VI B as the control class with each class containing 25 students. The research uses data collection techniques through post-tests in the form of multiple choice and descriptive questions, observation, documentation and interviews. The data obtained was analyzed using statistical tests which included normality tests, data analysis using the Paired Samples t-Test. Based on hypothesis testing calculations carried out using the t-test. Validity and reliability test results for all question items show valid and reliable results. The results of the normality test for learning outcomes are normally distributed, followed by using the Paired Samples t-Test, the results of the t-test for learning outcomes are at a sig value of 0.00 < α (0.05), so reject H0. So it can be concluded that there is an influence of the application of Powtoon learning media on student learning outcomes in class VI elementary school solar system material.